Collaborative Governance dalam Penanganan Pelanggaran Kampanye di Provinsi Kepulauan Riau - Shine Azizah Heply; Fitri Kurnianingsih; Firman Firman (Jurnal Relasi Publik, 2023)
This research refers to violations during the campaign period, specifically this settlement is regulated in Bawaslu Regulation Number 8 of 2018 concerning settlement of election administrative violations. The problem in implementing the campaign in this study is violations during the campaign. Violations of these rules will be considered criminal offenses and are subject to imprisonment for a maximum of 2 years. The research method used in this research is to use a qualitative descriptive approach with primary and secondary data sources as well as using data collection techniques by observation, interviews, and documentation. The theory in this study refers to Ansell and Gash namely, the results of the research show that in the first indicator, face-to-face dialogue is carried out with coordination meetings at a scheduled time, so that when campaigns reduce violations, fraud, violence and threats in the field. The second indicator of building trust is communication between organizers, supervisors and security personnel, and this is the keyword for successful collaboration. The third indicator is commitment to the process, namely the three parties involved carry out their roles, which means that the parties involved are committed to carrying it out. The fourth indicator in the process of mutual understanding is that the organizers, supervisors and security forces understand each other about the handling of violations during the campaign period. The fifth indicator is that the interim results in collaboration are carried out by the parties continuously trying to fulfill them properly, the interim results produce solutions and hopes from all parties by providing what is best for this country, and the creation of elections that are safe, peaceful and reduce fraud. The conclusion of this study is that the handling of campaign violations in the Riau Archipelago province will continue to be improved and improved and tighten supervision so that unwanted things do not occur and quality elections will be achieved.